Status of healthcare waste management in small and medium sized healthcare facilities in Nakuru East Sub County, Kenya - Kebati, Reuben; Mawenzi, Ramadhan L.; Justus, Osero (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care waste (HCW) is unwanted materials produced from hospitals, laboratories and research centres. HCW is of public health importance because hazardous HCW carries significant health risks. If poorly handled, it can lead to significant public health crises. Consequently, guidelines for proper management of HCW have been legislated. Unfortunately, not all healthcare facilities adhere to the guidelines. Diseases spread by inadequately disposed HCW are becoming increasingly prevalent especially in developing nations. This study was therefore conducted to establish the status of HCW management in six purposefully selected healthcare facilities in Nakuru East Sub-County (NESC), Kenya. Methods: A cross sectional study design was used to conduct this study. Six healthcare facilities (HCFs) in NESC, Kenya were purposefully selected. The HCFs were selected based on level and patient volumes and categorised as small or medium sized. HCW from each of the HCFs was weighed and categorised. Observation checklists and interviews were used to determine techniques used in HCW management. Results: The total weekly weight of HCW was 187.65 kg (mean 31.3 kg). Small sized HCF produced 49.55 kg/week while medium sized HCFs produced 138.1 kg/week. Total weekly weight of general HCW was 143.7 kg (76.5%); 33.8 kg (18%) was infectious while 10.2 kg (5.4%) was sharps. Conclusions: Healthcare facilities in NESC produce significant quantities of HCW. General HCW was predominant, followed by infectious waste and sharps. A considerable proportion of the HCFs did not comply with the stipulated guidelines for safe management of HCW. Concerned authorities in all HCFs should be alert and proactive regarding proper management of HCW.